Design of Digital Height Measurement Based Microcontroller AT89C51 - Tri Isra Janwardi (PT Inovasi Pratama Internasional, 2019)
Height measuring instrument is a tool that can be used by humans to assist in the process of determining height. Most height gauges in use today are analog or manual height gauges. In today's technological developments, the author will make an automatic height measuring device using ultrasonic sensors to calculate data from received objects. The sensor is used to measure the working distance at a frequency of 40 KHz so as not to interfere with human hearing. As the control center of this measuring instrument, it uses the Arduino Uno Microcontroller. This measuring instrument is capable of measuring an object with the accuracy of the sensor reading the data, namely the maximum height of 195 cm and the minimum height of 50 cm. The advantage of this tool is that it uses a microcontroller and sensor technology, while to display measurement results using an LCD and LCD measuring instruments can move according to the height of the object, to move the LCD a DC motor is used as the driver. And the measurement results are issued through the speaker in the form of sound that has been stored on the SD Card in WAV format, making it easier for blind people to know the user's height. The drawback of this tool is the construction of the tool and sensor readings, so that the results obtained from the measurements still contain some errors.